Short-Term Environmental Stimulation Spatiotemporally Modulates Specific Serotonin Receptor Gene Expression and Behavioral Pharmacology in a Sexually Dimorphic Manner in Huntington’s Disease Transgenic Mice - Zajac, Michelle S.; Renoir, Thibault; Perreau, Victoria M.; Li, Shanshan; Adams, Wendy; van den Buuse, Maarten; Hannan, Anthony J. (Frontiers in Molecular Neuroscience, 2018)
Huntington’s disease (HD) is a neurodegenerative disorder caused by a tandem repeat mutation encoding an expanded polyglutamine tract in the huntingtin protein, which leads to cognitive, psychiatric and motor dysfunction. Exposure to environmental enrichment (EE), which enhances levels of cognitive stimulation and physical activity, has therapeutic effects on cognitive, affective and motor function of transgenic HD mice. The present study investigated gene expression changes and behavioural pharmacology in male and female R6/1 transgenic HD mice at an early time-point in HD progression associated with onset of cognitive and affective abnormalities, following EE and exercise (wheel running) interventions. We have demonstrated changes in expression levels of the serotonin (5-HT) receptor Htr1a, Htr1b, Htr2a and Htr2c genes (encoding the 5-HT1A, 5-HT2B, 5-HT2A and 5-HT2C receptors respectively) in HD brains at 8 weeks of age, using quantitative real-time PCR. In contrast, expression of the serotonin transporter (SerT, also known as 5-HTT or Slc6a4) was not altered in these brains. Furthermore, we identified region-specific, sex-specific and environmentally regulated (comparing EE, exercise and standard housing conditions) impacts on gene expression of particular 5-HT receptors, as well as SerT. For example, SerT gene expression was upregulated by exercise (wheel running from 6-8 weeks of age) in the hippocampus. Interestingly, when EE was introduced from 6-8 weeks of age, Htr2a gene expression was upregulated in the cortex, striatum and hippocampus of male mice. EE also rescued the functional activity of 5-HT2 receptors as observed in the head-twitch test, reflecting sexually dimorphic effects of environmental stimulation. These findings demonstrate that disruption of the serotonergic system occurs early in HD pathogenesis and, together with previous findings, show that the timing and duration of environmental interventions are critical in terms of their ability to modify gene expression. This study is the first to show that environmental enrichment is able to selectively enhance both gene expression of a neurotransmitter receptor and the functional consequences on behavioural pharmacology, and links this molecular modulation to the therapeutic effects of environmental stimulation in this neurodegenerative disease.